Evidence From a Long-Term, Systematic Post-Market Surveillance Program: Clinical Performance of a Hematocrit-Insensitive Blood Glucose Test Strip. (January 2021) - Setford, Steven; Phillips, Stuart; Grady, Mike
Background: Described is a manufacturer's systematic post-market evaluation of the long-term clinical accuracy of a commercially available blood glucose monitoring (BGM) test strip product. Methods: Production batches of test strips were routinely and regularly sampled and evaluated in a clinical setting to assess product accuracy. Evaluations were performed on capillary blood samples from a minimum of 100 subjects with diabetes, by clinical staff according to instructions for use. Readings were compared against capillary blood samples collected at the same time and measured by a standard laboratory reference method. Clinical accuracy was calculated according to EN ISO 15197:2015. Results: A total of 21 115 paired results were obtained, equating to 209 production batches over the >3-year period since test strip launch. Of the results, 97.6% met the accuracy criterion (range: 97.1-98.1% by year), with 98.1% of values presenting zero risk as defined by the surveillance error grid. At the <5th (21.0-33.8%) and >95th (48.3-59.4%) percentile extremes of hematocrit distribution, 97.9% and 96.4% of values were clinically accurate. The product also demonstrated clinical accuracy across all seven glucose ranges ("bins") as defined by the standard. Under conditions of combined hematocrit and glucose (<80 mg/dL and ≥300 mg/dL) extremes, 97.7% of values were clinically accurate. Conclusions: Methodologies and results from a manufacturer's self-imposed clinical accuracy surveillance program of a BGM product is presented. Given the publication of sometimes-conflicting data presented within ad hoc BGM clinical accuracy evaluations, usually of limited size, it is advocated that BGM manufacturers adopt similarly robust and systematic surveillance programs to safeguard patients.